Diverse functionalization of strong alkyl C–H bonds by undirected borylation - Oeschger, Raphael (Science, 2020)
The selective functionalization of strong, typically inert carbon-hydrogen (C–H) bonds in organic molecules is changing synthetic chemistry. However, the undirected functionalization of primary C–H bonds without competing functionalization of secondary C–H bonds is rare. The borylation of alkyl C–H bonds has occurred previously with this selectivity, but slow rates required the substrate to be the solvent or in large excess. We report an iridium catalyst ligated by 2-methylphenanthroline with activity that enables, with the substrate as limiting reagent, undirected borylation of primary C–H bonds and, when primary C–H bonds are absent or blocked, borylation of strong secondary C–H bonds. Reactions at the resulting carbon-boron bond show how these borylations can lead to the installation of a wide range of carbon-carbon and carbon-heteroatom bonds at previously inaccessible positions of organic molecules.